2013
DOI: 10.1242/dev.091793
|View full text |Cite
|
Sign up to set email alerts
|

Sox proteins: regulators of cell fate specification and differentiation

Abstract: SummarySox transcription factors play widespread roles during development; however, their versatile functions have a relatively simple basis: the binding of a Sox protein alone to DNA does not elicit transcriptional activation or repression, but requires binding of a partner transcription factor to an adjacent site on the DNA. Thus, the activity of a Sox protein is dependent upon the identity of its partner factor and the context of the DNA sequence to which it binds. In this Primer, we provide an mechanistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
430
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(456 citation statements)
references
References 199 publications
14
430
0
4
Order By: Relevance
“…SOX proteins are an evolutionarily ancient family of complex-forming transcriptional activators and repressors that are identified by a conserved HMG DNA-binding domain [26,27]. A plethora of SOX genes has been demonstrated to be expressed within the developing pancreas, including most of the C, D, E, F, G and H subfamily members [28].…”
Section: Introductionmentioning
confidence: 99%
“…SOX proteins are an evolutionarily ancient family of complex-forming transcriptional activators and repressors that are identified by a conserved HMG DNA-binding domain [26,27]. A plethora of SOX genes has been demonstrated to be expressed within the developing pancreas, including most of the C, D, E, F, G and H subfamily members [28].…”
Section: Introductionmentioning
confidence: 99%
“…Among progenitor cell markers of interest are also SOX (Sry-related HMG-Box gene) proteins. Some represent nuclear transcription factors in the differentiation of neural crest progenitor cells to melanocytes, while others are more versatile regulators of stem and progenitor cell fate (72,73). The immunohistochemical profile of SOX10 was used to detect metastatic melanoma in sentinel lymph nodes with high sensitivity and specificity and is supposed to be a reliable marker for supplementing other immunohistochemical stains, like S100B or melan-A (74).…”
Section: Progenitor And/or Stem Cell-like Markersmentioning
confidence: 99%
“…Though the ChIP-seq data we used did not list ASCL1 as an experimentally determined target, literature review has revealed that FOXP2 strongly represses ASCL1 [74]. Additionally, the joint regulation of the common target SOX21 by miR-3666 and FOXP2 maintains the balance of SOX2 and SOX21 activities that, in turn, is required for the balance of progenitor cell maintenance and the progression to postmitotic neural development [75,76].…”
Section: Mir-3666 Directly or Indirectly Regulates Foxp2 Functions Inmentioning
confidence: 99%